Expression of human epidermal growth factor receptor 2 in meningiomas - Mazaher Ramezani; Hanieh Firoozabadi; Mansour Rezaei; Sedigheh Khazaei; Masoud Sadeghi (Indian Journal of Medical and Paediatric Oncology)
Background: Meningiomas consist of 15%–30% of the primary intracranial tumors, and high-grade meningiomas have a higher recurrence after surgery. The human epidermal growth factor receptor 2 (HER2) status is important in the medical management of patients with various human cancers. This study aimed to evaluate HER2 expression in meningiomas and the correlation between this expression and age, gender, and grade. Materials and Methods: In a descriptive-analytic study, immunohistochemistry (IHC) with HER2 marker was done on confirmed cases of meningioma which were referred to the pathology laboratory from 2008 to 2015. The primary antihuman antibody against c-erbB-2 oncoprotein (DAKO Diagnostics) was used for IHC. Results: Of 117 patients, 68.4% were males. The mean age of the patients was 53.6 years. Grades I, II, and III tumors were 90.6%, 8.5%, and 0.9% of cases, respectively. Totally, 76 (65%) of patients were HER2 positive, with only 7.7% of highly expressed HER2. There was no significant correlation between the mean age (P = 0.672), age group (P = 0.256), sex (P = 0.574), and grade (P = 0.093) and HER2 expression status. Conclusions: We did not find a statistically significant correlation between age, sex, or grade and HER2 status; however, further studies with a higher number of Grades II and III meningiomas and using the fluorescent in situ hybridization in equivocal cases may be of benefit in this way.